Histomorphological analysis of phyllodes tumors at a tertiary care center - Swathi Samalla; Motrapu Lavanya; Mohd Imran Ali; Smitha Vadana SP (Asian Journal of Medical Sciences, 2023)
Background: Phyllodes tumors (PT) are rare biphasic neoplastic breast lesions. They account for 0.3–0.5% of female breast tumours1 and have an incidence of about 2.1 per million, the peak of which occurs in women aged 45–49 years. There is sometimes difficulty in dividing tumors into the three recognized grades based on histomorphological features. It is because of the subjective variation and absence of a definitive grading system. More importantly, they do not always correlate with clinical outcome in terms of predicting recurrence, malignant transformation, metastasis, and overall survival. Aims and Objectives: (1) The aim of the study was to study the clinicopathological and histomorphological features of the PT and classify the tumors based on 2019 WHO classification. Materials and Methods: This study was done in the Department of Pathology at Government General Hospital Nizamabad. Total 68 cases are included in this study over a period of 5 years (3 1⁄2 years retrospective and 11/2 year prospective) from 2017 March to 2022 March. PT cases were analyzed based on 2019 WHO classification criteria. The age of the patients, tumor locations, and the relevant details were obtained from the pathology records. Results: Of the 68 PT cases, 53 (78%) were classified as benign, 8 (12%) borderline and 7 (10%) malignant PT based on histomorphological features based on 2019 WHO classification. Conclusion: Our study showed that tumors occurring in older age group with a large tumor size and the presence of malignant heterologous elements, infiltrating borders, and surgical margins <1 cm were usually malignant phyllodes.